The Antibiotic Prescribing Practices of Gynecologists in Abdominal Hysterectomy - Khoirunnisa Novitasari; Tjokroprawiro, Brahmana Askandar; Ulhaq, Renata Alya; Aldika Akbar, Muhammad Ilham (Indonesian Socety of Obstetrics and Gynecology, 2024)
Objective: To evaluate the pattern of antibiotics used for abdominal hysterectomy by gynecologists in infected and non-infected cases. Methods: Data was collected through an online survey of gynecologists in Surabaya, Indonesia. Results: A total of 200 gynecologists were involved in this study. All of them used prophylactic antibiotics in all cases of abdominal hysterectomy, and the most commonly used was cefazoline (70.5%), followed by ceftriaxone (15.5%) and cefotaxime (9%). Most gynecologists (68%) gave 2 grams of prophylactic antibiotic, and 79,5% of antibiotics were administered within 30 minutes before surgery. Additional antibiotics during surgery were given in prolonged surgery (79.01%) and intraoperative bleeding > 1500 mL (48.14%). The most common additional dosage used was 1 gram (72.9%), and most gynecologists (37.2%) continued antibiotics for one day ahead. The type of therapeutic antibiotics used for infected cases was varied, consisting of ceftriaxone (50.5%), metronidazole (42%), cefotaxime (17%), cefazoline (15.5%), gentamicin (12%), ampicillin-sulbactam (4%), and amoxicillin-clavulanic acid (3.5%). Most gynecologists (43.7%) gave these antibiotics for three days. Conclusion: The majority of gynecologists in Surabaya already use prophylactic antibiotics for abdominal hysterectomy and therapeutic antibiotics for infected cases following the existing guidelines